Impact Lingkungan Dalam Pendidikan - Arif, Mohammad (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2015)
Environmental education is one of the factors which includes natural conditions and this world with certain ways can influence our behavior, growth and development or life processes. Environment is all that is both human and manmade or natural objects that move, events or things that has a relationship with someone. the role of parents in the family as a guide, teacher, and giving examples. During the preschool years, relationships with parents or guardians are the basis for social and emotional development of children. society as providers of education, both instituted (school track and outdoor track schools) as well as non-institutionalized pathways (pathways outside of school). institution community organizations and / or social groups in the community, either directly or indirectly involved has a role and educative function. Progress of society and the rapid development of science and technology, as well as the strengthening of globalization will influence the roles and functions between the educational environment. In addition to a shift in the role also demanded an increase in the quality of the part.